1995
DOI: 10.1111/j.1365-2389.1995.tb01337.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analysis of a soil microbial community in a soybean field

Abstract: Summary We report here the phylogenetic characterization of small subunit rRNA gene sequences obtained by polymerase chain reaction (PCR) amplification of mixed population DNA extracted directly from soil in a soybean field without culturing the organisms. The phylogenetic analysis of 17 soil clones by the neighbour‐joining method shows that the soil sample contained broadly diverse prokaryotes; a clone related to archaea, a clone to gram‐positive bacteria with high G+C contents, two clones to green sulphur ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
2
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 32 publications
7
115
2
4
Order By: Relevance
“…The DNA extraction method described by Ueda et al (1995) was used with some modifications. We mixed approximately 20 g of sediment with an equal volume of 120 mM sodium phosphate buffer (pH 8.0) containing 5% SDS; the mixture was vigorously shaken in a plastic bottle for 40 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA extraction method described by Ueda et al (1995) was used with some modifications. We mixed approximately 20 g of sediment with an equal volume of 120 mM sodium phosphate buffer (pH 8.0) containing 5% SDS; the mixture was vigorously shaken in a plastic bottle for 40 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…1992, DeLong et al 1994, McInerney et al 1995a, b. Preston et al 1996. Relatives also include 2 soil archaeal clones (Ueda et al 1995;see also RDP, Maidak et al 1994) as well as clones recently found in freshwater lake sediments (Hershberger et al 1996). The second group falls among the Euryarchaeota (contaming methanogens, halophiles, and some thermophiles; Woese 1987), is distantly related (<80'% sequence similarity) to Thermoplasma, and has also previously been reported from coastal and offshore marine plankton (DeLong 1992.…”
Section: Archaeamentioning
confidence: 99%
“…Also, short 16s rDNA clone sequences from a paddy field (Maidak et al, 1994), a soybean field (Ueda et al, 1995) and a marine environment (Fuhrman et al, 1993) were demonstrated to cluster with these actinobacterial sequences. Thus it has been concluded that this group of uncultured organisms might contribute to ecologically important processes (Rheims et al, 1996b).…”
Section: Introductionmentioning
confidence: 99%